Ethnicity, information and cooperation: Evidence from a group-based nutrition intervention - Raghunathan, Kalyani; Alvi, Muzna; Sehgal, Mrignyani (Elsevier, 2023)
Development programs often rely on locally hired agents for service delivery, especially for interventions promoting agricultural practices, health, and nutrition. These agents are key to reaching underserved communities, especially women, with information and services around recommended practices. However, where societies are socially stratified, differences in ethnic identities between agents and beneficiaries may impact the effectiveness of information and service delivery and the uptake of recommended behaviors. We explore the salience of shared ethnic identity between agents and beneficiaries in promoting collective action using a field experiment with women’s self-help groups (SHGs) in India. We cross-randomize an information treatment and a group-agent shared ethnicity treatment at the SHG level. We measure impacts on individual group member information retention and willingness to contribute to a group-owned kitchen garden that could improve access to a diverse and nutritious diet. We find information retention is better when the group is matched with an agent lower in the ethnic hierarchy, but that agents higher in the hierarchy elicit greater individual contributions to the group-owned kitchen garden. We suggest some hypotheses for these seemingly contradictory results. Other characteristics like education, group cohesion and perceived agent ability also matter in changing knowledge and contribution. Our findings have important implications for effective program design and implementation, suggesting that implementers need to consider factors beyond the information content, target group and pedagogical mode of delivery for their strategies to be transformative.